Pandangan Al-Qur’an Terhadap Bigetisme Yahudi dan Kristen - Hamim Ilyas (Al-Jami'ah Research Centre, 1998)
The Qur'ān criticizes ahl al-kitāb–Jews and Christians–in many verses. One of the subjects being criticized by the Qur'ān is the idea of begetism -God begets children. The Qur'an teaches us that the Jews and the Christians regard 'Uzayr and 'Isa respectively as the sons of God. For some scholars, the Qur'ānic statement is equivocal, and thus becomes a controversial issue in the theological discourse. The current essay is devoted to debate the idea of begetism, and identifies the followers of begetism among the Jews and Christians who are being criticized by the Qur'ān. In order to carry through the purpose, the author employs exegetical approaches to analyze the issue thematically. In the end, the author concludes that the Qur'ānic criticism toward begetism is some sort of warning (indhār) to the Jews and Christians- as recipients of previous revelations.